CAN INDUSTRIALIZATION AFFECT HEAVY METALS BIOCONCENTRATION IN DATE PALM TREE FARMS IN THE SULTANATE OF OMAN? - & et al., Al-Shali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Purpose Industrialization is leading to gradual accumulation of heavy metals in the date palm fruits and ecosystem. This paper aims at estimating the bioaccumulation of heavy metals in soils, fruits (dates) near the industrial area of Al-Rusail in the Sultanate of Oman. There were three sites located for sampling and each with three farms except site 3 with one farm; industrial site, cement factory and control farm. The soil, water and date palm fruits were analyzed for heavy metals concentration using inductively coupled plasma optical emission spectrometer. The results of analysis showed that the mean concentration of heavy metals in soil was in the following order: Ni> Zn > Pb > Cd. The concentration of heavy metals in the groundwater was found to be in this order Zn > Ni> Pb> Cd, and Zn> Pb > Ni > Cd in fruits. The statistical interaction of heavy metal mean concentrations indicated cadmium with the highest mean (0.007117mg/kg) in Farm 1 during the month of June at 0-30cm (mg/kg) in soil under Industrial sites. The fruit stages differ statistically with the highest concentration of zinc ranging from 0.190517 mg/Kg of khalal stage of farm 1 to the 0.03127 mg/kg of the control farm. groundwater heavy metal concentration was very low across the farms with the least (Cd at 0.0002434mg/Kg) in control site and not statistically different from other sites’ farms.In general, the research indicated an increases in the heavy metal concentrations with closeness to industrial sites.